2007
DOI: 10.1902/jop.2007.060089
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of “De Novo” Plaque Formation With 0.12% Chlorhexidine Spray Compared to 0.2% Spray and 0.2% Chlorhexidine Mouthwash

Abstract: Within the limitations of this 3-day "de novo" plaque formation study, the two sprays were not as effective as the mouthwash in plaque inhibition. No significant difference was found between the two sprays. To achieve the same effectiveness as a mouthwash, a higher dose (number of puffs) of CHX spray may be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 37 publications
2
23
0
1
Order By: Relevance
“…In initially plaque‐free surfaces, CHX did not stop plaque growth totally. This tendency of increasing plaque scores on initially plaque‐free surfaces was expected as demonstrated in other studies 38,43,55,56 . However, after day 11, initially plaque‐covered surfaces showed a statistically significant decrease in plaque scores.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In initially plaque‐free surfaces, CHX did not stop plaque growth totally. This tendency of increasing plaque scores on initially plaque‐free surfaces was expected as demonstrated in other studies 38,43,55,56 . However, after day 11, initially plaque‐covered surfaces showed a statistically significant decrease in plaque scores.…”
Section: Discussionsupporting
confidence: 87%
“…CHX was selected as the test substance because it is the best characterized and most effective chemical antiplaque agent 38,41,44 . The concentration selected (0.12%) corresponds to that used clinically for substitutive plaque control.…”
Section: Discussionmentioning
confidence: 99%
“…It is emphasized that no instructions on prophylaxis or dental hygiene and diet were performed prior to the present study or during analysis. Hence, this study confirmed the strong antimicrobial potential of chlorhexidine against structured microbial communities, as seen in previous reports [2,20,21].…”
Section: Discussionsupporting
confidence: 92%
“…A causa da DP é a placa bacteriana (PB) (Löe 1967), que se estabelece entre 24-48 horas após a profilaxia da superfície dental (Gioso 2007). Se o acúmulo da PB não for controlado, ocorre progressão da DP, em geral sem regeneração e incurável devido à resposta inflamatória individual que resulta em destruição do periodonto com perdas funcional e dentária (Harvey & Emily 1993, DuPont 1997, Stoeken et al 2007). Complicações sistêmicas devidas à bacteremia e absorção de toxinas bacterianas oriundas da cavidade oral são relatadas como possíveis responsáveis por alterações no coração, nos rins, no fígado (Debowes et al 1996) e nas articulações (Gioso 2007).…”
Section: Introductionunclassified